The emotional power of sound: how soundtracks shape listeners' experiences and bring people closer to the musical environment (Olhares, 2025)
Abstract: The central idea for this research emerged after hearing audience reports after a concert on the theme of "Striking Soundtracks" with the Voz&Arte Choir, of which I have been a member for three years. The research investigates how soundtracks can be used as an expressive tool in stage and musical creation with young people, stimulating active listening, affective memory, and creativity. The study begins with the context of young people's constant exposure to audiovisual productions and seeks ways to critically and creatively appropriate these resources in the school environment. It is based on Koelsch (2011), on music and memory; Suzel Reily (2014), on music and memory practices; and Tragtenberg (1999), on sound dramaturgy. The work develops on two fronts: a theoretical analysis of the expressive and symbolic aspects of soundtracks on stage and the production of a documentary, in the final editing phase, with interviews with professionals in the field.Keywords: Sound on stage; Affective memory; Experience; Sensitive pedagogy.